No hearing without signals: imagining and reimagining transductions through the history of the cochlear implant. (2nd September 2021) - Lloyd, Stephanie; Tremblay, Alexandre
ABSTRACT: In this article, we explore a set of conceptual and technoscientific shifts that led to reconsiderations of the experience of hearing over the twentieth and twenty-first centuries, and most specifically, hearing through the use of cochlear implants (CIs). In doing so, we focus on the factors that are thought to contribute to CI users' experiences of sound, including their potentially distinctive sensoria and neural profiles, as they navigate the spaces of their day-to-day lives as both the bearers of objective audiograms and subjective listeners. These factors are increasingly broad, ranging from age of implantation, electroacoustic stimulation sent from the device, and cognitive profiles considered to correlate with complex developmental processes related to early sound environments and language exposure (oral or manual). Hearing, in this perspective, is a phenomenon that varies between individuals, over the course of the life (or day) of a single person, and according to experiences with auditory devices. Such a conceptualization undermines dichotomous representations of hearing and deafness and an increasingly substantial gray zone emerges between the two. Both are ever more conceived of as developmental processes in which a variety of signals and their transductions are considered central to understandings of how experiences of hearing take shape.